STUDI KORELASI INDEKS MASSA TUBUH (IMT), POLA AKTIVITAS FISIK, DAN STATUS HIPERTENSI DENGAN KEJADIAN DIABETES MELLITUS TIPE II - Utami, Kurniati Dwi; Suwardiman, Suwardiman; Sutrisnawati, Ika; Hendrik, Hendrik; Annisa, Nurul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Diabetes Mellitus (DM), often referred to as diabetes, is a metabolic disease characterized by elevated blood glucose levels above normal. Based on data from the Medan City Health Office, the number of T2DM increases every month by around 699 cases as well as the incidence of metabolic disorders which continues to increase due to diabetes. Puskesmas Glugur Darat is one of the health centers with the highest number of T2DM patients in Medan city. Based on the results of the recapitulation of the monthly report on T2DM disease obtained from the Medan City Health Office in 2019, in one month the number of T2DM can reach 282 patients. The purpose of the study was to determine the correlation of body mass index (BMI), physical activity patterns, and hypertension status with the incidence of type II diabetes mellitus. The type of research is quantitative with a case control approach. The sample consisted of 88 case samples and 88 control samples. The sampling technique used Simple Random Sampling. The results showed that there was a relationship between BMI (p value: 0.009), physical activity patterns (p value: 0.030) and hypertension status (p value: 0.001) on the incidence of diabetes. It is recommended to the health center to disseminate information and education through print and electric media in the form of bulletins, and conduct regular health screenings to a group of high-risk communities.Keywords: Physical Activity, Diabetes, Hypertension